Pathophysiological problems of residual ovary - Molina Navia, Lucas (2015)
Physiopathological problems related to residual ovary as seen to day by the trends of the functional gynecological surgery are discussed. The main cause of the residual dysfunction results from impairment in the circulation and neuro-trophic system. Fragments of the ovaries left which by their size are equivalent to ovarian grafts produce serious changes in the ovary-pituitary- endometrium, endocrine balance.